The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.15193/zntj/2011/79/005-023
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Spray-Dried Emulsions Stabilised by Milk Proteins

Abstract:  CHARAKTERYSTYKA SUSZONYCH ROZPYŁOWO EMULSJI STABILIZOWANYCH BIAŁKAMI MLEKAS t r e s z c z e n i e W opracowaniu przedstawiono zagadnienia z zakresu suszenia rozpyłowego emulsji typu olej w wodzie, stabilizowanych białkami mleka. Omówiono rolę składników emulsji (cukrów i białek mleka) w tworzeniu matrycy cząstek podczas suszenia rozpyłowego oraz opisano te cechy sproszkowanych emulsji, które są powiązane z formą proszku (zwilżalność, sypkość, podatność na zbrylanie). Przedstawiono dane dotyczące efektywności… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Their size for all four fractions ranged from 3.10 to 45.21 µm, with the average size ranging from 18.86 to 25.49 µm, and their state of aggregation remained consistent. According to Domian [44], these observations confirm the stability of the obtained emulsion. Due to the surface properties, milk proteins play a primary function as emulsion-stabilizing colloids.…”
Section: Jojoba Oil Droplet Particle Size and Distribution In Hydroge...supporting
confidence: 72%
“…Their size for all four fractions ranged from 3.10 to 45.21 µm, with the average size ranging from 18.86 to 25.49 µm, and their state of aggregation remained consistent. According to Domian [44], these observations confirm the stability of the obtained emulsion. Due to the surface properties, milk proteins play a primary function as emulsion-stabilizing colloids.…”
Section: Jojoba Oil Droplet Particle Size and Distribution In Hydroge...supporting
confidence: 72%
“…Structural differences within milk protein molecules affect their properties [39]. It is assumed that β-casein is the most effective stabilizer among milk proteins as it reduces the surface tension most [40].…”
Section: Samplementioning
confidence: 99%
“…This could be because the sucrose components formed a glassy outer layer on the nanofibers. Studies on spray dried and freeze dried microcapsules containing sugars have found that low molecular weight sugars form a glassy coating around the microcapsules upon rapid drying [37][38][39][40]. Moreover, the sucrosecontaining systems produced significantly thicker fibers, which could be attributed to the glassy coating of sugar formed (tables 1, S2).…”
Section: Bacteriophage Nanofiber Morphologymentioning
confidence: 99%